Pemetaan Kawasan Rawan Banjir dan Longsor Berbasis Sistem Informasi Geografis di Kabupaten Sijunjung - Dwi Marsiska Driptufany; Herlan Roy Andika; Fajrin Fajrin; Defwaldi Defwaldi; Ilham Armi (Jurnal Sains dan Ilmu Terapan, 2025)
Sijunjung Regency is one of the regencies in West Sumatra Province which is located in an area prone to landslides, earthquakes, fires and floods. Floods and landslides often occur due to changing river flow patterns, erosion and sedimentation in the Batang Ombilin, Batang Sukam, and Batang Palangki rivers, as well as the geology of Sijunjung Regency which mostly consists of rocks. This study aims to map the spatial distribution of areas prone to floods and landslides in Sijunjung Regency based on Geographic Information Systems (GIS) using scoring and weighting methods as well as parameters that compose the vulnerability which are then overlay. The parameters used in the analysis include land use, slope gradient, land elevation, rainfall, soil type, rock type and river network. The data used comes from administrative maps, spatial data, and regional hydrological and climatological information. The research found that flood-prone areas in Sijunjung Regency are dominated by moderate areas 68%, high areas 9%, and low areas 23%. The verification rate was 75%.